2019
DOI: 10.1038/s41598-018-38403-8
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Superconductivity with Sr-Deficiency in Antiperovskite Oxide Sr3−xSnO

Abstract: Bulk superconductivity was recently reported in the antiperovskite oxide Sr3−xSnO, with a possibility of hosting topological superconductivity. We investigated the evolution of superconducting properties such as the transition temperature Tc and the size of the diamagnetic signal, as well as normal-state electronic and crystalline properties, with varying the nominal Sr deficiency x0. Polycrystalline Sr3−xSnO was obtained up to x0 = 0:6 with a small amount of SrO impurities. The amount of impurities increases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 39 publications
2
33
0
Order By: Relevance
“…We comment that the phase splitting into the nearly stoichiometric and deficient compounds has been suggested in the previous study of magnetization [16] and indeed observed with NMR [15]. Since NMR probes properties of the conduction electrons though it measures the Zeeman energy of the Sn nucleus, the splitting in the NMR spectrum suggests that one sample consists of two materials ("phases") with distinct stoichiometries as shown in Fig.…”
Section: Comparison With Nmrsupporting
confidence: 68%
See 2 more Smart Citations
“…We comment that the phase splitting into the nearly stoichiometric and deficient compounds has been suggested in the previous study of magnetization [16] and indeed observed with NMR [15]. Since NMR probes properties of the conduction electrons though it measures the Zeeman energy of the Sn nucleus, the splitting in the NMR spectrum suggests that one sample consists of two materials ("phases") with distinct stoichiometries as shown in Fig.…”
Section: Comparison With Nmrsupporting
confidence: 68%
“…Due to the recent predictions of bulk Dirac cones [3,4] and topological nature [5] in the vicinity of the Fermi energy, antiperovskite oxides are attracting a lot of attention [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. After the initial theoretical predictions, the chemical and physical characters of antiperovskite oxides have been extensively investigated [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimentally, angle-resolved photoemission spectroscopy [11], magnetotransport [12,13] and nuclear magnetic resonance [14] measurements have probed the possible 3D Dirac nature of the electrons in these compounds. Experiments have also revealed signatures of ferromagnetism arising from oxygen vacancies [15,16], high thermoelectric performance [17], superconductivity arising from Sr vacancies [18,19] and weak antilocalization due to spin-orbital entanglement [20]. The rich electronic properties of the antiperovskites take as their fundamental origin the unusual valence state of B (= Sn, Pb).…”
Section: Introductionmentioning
confidence: 99%
“…When A is a group-2 element and B is tin or lead, the valence of the B ion becomes 4− to satisfy the charge neutrality condition [6]. Indeed, Sn 4− state was experimentally confirmed in Sr 3−x SnO by Mössbauer measurements [7]; such a negative-ionic state of a metallic element is quite unusual.…”
mentioning
confidence: 99%